PELATIHAN PEMBUATAN KRUPUK IKAN EKOR KUNING SEBAGAI IDE BISNIS DALAM MENGEMBANGKAN JIWA WIRAUSAHA PADA DESA MUARA GADING MAS LAMPUNG TIMUR - Ayu, Raden; Diah, Hartini; Ahmad, Julian (Publika Citra Media, 2024)
Lack of knowledge and skills in processing fishery products, namely those that can become products of economic value. So this Community Service aims to increase the knowledge and skills of the group of women in Muara Gading Mas village through training in making crackers made from fish as the basic ingredient into savory and delicious processed fish cracker products. The target of this program is the formation of a business unit that develops food products from fish as basic ingredients. Specifically, this program aims to train housewives in Muara Gading Mas village to produce fish crackers. This training is providedstarting from processing methods, drying methods to frying. The results achieved in this activity are that the group of housewives in Muara Gading Mas village understand and have skills in entrepreneurship, and know how to manage abusiness in a more structured way, there are fish cracker products with a savory and delicious taste. From the results of the evaluation that has been carried out, it can be seen that the participants' knowledge regarding fish-based processing hasincreased and opened the participants' minds to take advantage of existing opportunities to increase income.